Fertility-Sparing Management for Bulky Cervical Cancer Using Neoadjuvant Transuterine Arterial Chemotherapy Followed by Vaginal Trachelectomy. Issue 6 (1st July 2012) - Tsubamoto, Hiroshi; Kanazawa, Riichiro; Inoue, Kayo; Ito, Yoshihiro; Komori, Shinji; Maeda, Hiroaki; Hirota, Shozo
Abstract : Background: Fertility-sparing management for bulky cervical cancer remains under investigation. We investigated the safety of neoadjuvant transuterine arterial chemotherapy (TUAC) followed by a simple vaginal trachelectomy for patients with tumors larger than 3 cm in diameter who desired uterine preservation. Methods: First, to assess the safety and efficacy of TUAC, survival and pathological complete response data from 39 patients with a diagnosis of stage IB2 to stage IIB cervical cancer who participated in 2 consecutive trials during 1997–2006 were analyzed. The neoadjuvant chemotherapy regimens were a combination of TUAC using cisplatin with intravenous nedaplatin or irinotecan. Second, to assess the safety of fertility-sparing management with TUAC, medical records of patients matching the following criteria were reviewed during the same period: (1) International Federation of Gynecology and Obstetrics stages IB1 to IIA; (2) maximum diameter of tumor, 3 cm or more; (3) squamous cell carcinoma; (4) no radiological findings of lymph node metastasis; and (5) patient's strong desire for preservation of the uterus and to undergo TUAC. Results: The overall 5-year survival rate of the 39 enrolled patients was 81.0% (95% confidence interval, 64.8%–93.7%). No malignant cells were found in pathologically examined surgical specimens from 14 patients (35.9%), all of whom were alive without recurrence for more than 7 years after treatment. Based on medical records, 7 patients were eligible according to the fertility-sparing criteria, 1 patient with International Federation of Gynecology and Obstetrics stage IB1 cancer, 5 patients with stage IB2, and 1 patient with stage IIA. One patient with stage IB1 cancer and 2 patients with stage IB2 cancer underwent simple vaginal trachelectomy, resection of paracervical tissues, and abdominal lymphadenectomy. Their disease-free intervals were 86, 120, and 65 months, respectively. All 3 patients had regular menses after surgery but no pregnancies, for personal reasons unrelated to fertility. Conclusions: Powerful neoadjuvant chemotherapy regimens resulted in a pathological complete response. Long-term disease-free interval was achieved after fertility-sparing management for bulky cervical cancer in 3 cases.